2015
DOI: 10.1051/0004-6361/201526930
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the emission profile of an H2discharge lamp to simulate interstellar radiation fields

Abstract: Context. Microwave discharge hydrogen-flow lamps have been used for more than half a century to simulate interstellar ultraviolet radiation fields in the laboratory. Recent discrepancies between identical measurements in different laboratories, as well as clear wavelength dependent results obtained in monochromatic (synchrotron) experiments, hint at a more elaborate dependence on the exact discharge settings than assumed so far. Aims. We have investigated systematically two lamp geometries in full dependence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 30 publications
(52 reference statements)
1
42
0
Order By: Relevance
“…Muñoz Caro et al (2010) determined a desorption yield for pure CO ice of (3.5 ± 0.5 × 10 −2 ) photon −1 which is one order of magnitude higher than that from Öberg et al (2009a). Recent investigations showed that the FUV spectrum, in particular the ratio of Lyman-α (121.6 nm) to H 2 molecular emission bands (110-180 nm), is sensitive to the gas pressure, the type of lamp, the gas composition (pure H 2 versus a mixture of H 2 and He) and the window properties (Chen et al 2014;Ligterink et al 2015). Chen et al (2014) determined CO desorption yields as high as (2.12 ± 0.03 × 10 −1 ) photon −1 for a lamp setup with pure H 2 and a window giving a ratio of 20 % flux of Lyman-α relative to the molecular emission bands.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Muñoz Caro et al (2010) determined a desorption yield for pure CO ice of (3.5 ± 0.5 × 10 −2 ) photon −1 which is one order of magnitude higher than that from Öberg et al (2009a). Recent investigations showed that the FUV spectrum, in particular the ratio of Lyman-α (121.6 nm) to H 2 molecular emission bands (110-180 nm), is sensitive to the gas pressure, the type of lamp, the gas composition (pure H 2 versus a mixture of H 2 and He) and the window properties (Chen et al 2014;Ligterink et al 2015). Chen et al (2014) determined CO desorption yields as high as (2.12 ± 0.03 × 10 −1 ) photon −1 for a lamp setup with pure H 2 and a window giving a ratio of 20 % flux of Lyman-α relative to the molecular emission bands.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Photodesorption of the ice is induced using VUV photons produced by a microwave H 2 discharge lamp. The lamp (borosilicate) has a F-type design (Ligterink et al 2015), and is evacuated using a scroll pump. The plasma is powered by a Sairem microwave generator using an Evenson cavity.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Therefore, the SED of the microwave powered H 2 -discharge lamp is used as characterised recently, using an absolute calibrated VUV spectrometer (Ligterink et al 2015). The resulting spectrum has been presented in Paardekooper et al (2016).…”
Section: Photon Flux Calibrationmentioning
confidence: 99%
See 2 more Smart Citations